MODEL PENINGKATAN KINERJA SUMBER DAYA MANUSIA BERBASIS BUDAYA ORGANISASI, JOB INVOLVEMENT DAN ORGANIZATIONAL BEHAVIOR-ALTRUISM PADA SEKRETARIAT DPRD KAB. KOLAKA SULAWESI TENGGARA - Sugianto Sugianto (Jurnal Riset Bisnis Indonesia, 2015)
This research is designed to examine the effect of organizational culture and job involvement on humanresource performance through OCB-altruism in DPRD Secretariat of Kolaka Regency of South EastSulawesi. After distributing relevant questionnaires among 72 employees, all usable questionnairesare returned. Then the data collected are analyzed by using Structural Equation Modeling withSmartPLS verse 3. Research results show that no significant direct effect between organizationalculture and human resource performance, but an indirect effect between organizational culture andhuman resource performance with OCB-altruism acting as a mediator. Furthermore job involvementnot only has a positive significant effect on OCB-altruism, but also on human resource performance.While OCB-altruism also has a positive significant effect on human resource performance.Keywords: Organizational Culture, Job Involvement, OCB-altruism, Human Resource Performance